2004
DOI: 10.1103/physrevb.69.060401
|View full text |Cite
|
Sign up to set email alerts
|

Change in Mn3dorbital state related to a metal-insulator transition in a bilayer manganite studied by magnetic Compton profile measurement

Abstract: Temperature dependence of magnetic Compton profile ͑MCP͒ has been measured on a single crystal of La 2Ϫ2x Sr 1ϩ2x Mn 2 O 7 at xϭ0.42 along the c-axis. The spin magnetic moments of Mn 3d electrons in t 2g and e g type orbitals are evaluated from the line-shape fitting analysis of MCP's using theoretical profiles derived from the (MnO 6 ) 8Ϫ ab initio calculations. The experimental ratios of e g spins to t 2g ones show higher values above the metal-insulator transition temperature T c in comparison with the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…1 fail to reproduce the experimental MCP's, because the hybridization between Mn-3d and O-2p orbitals affects the profiles, and is not included in the atomic profiles. Then, we prepared theoretical profiles suitable for the line-shape analysis by using an ab initio molecular orbital calculation for the (MnO 6 ) 8K cluster [15,16]. In the calculation, the cluster was embedded in 913-point charges in total that describe the Madelung potential.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 fail to reproduce the experimental MCP's, because the hybridization between Mn-3d and O-2p orbitals affects the profiles, and is not included in the atomic profiles. Then, we prepared theoretical profiles suitable for the line-shape analysis by using an ab initio molecular orbital calculation for the (MnO 6 ) 8K cluster [15,16]. In the calculation, the cluster was embedded in 913-point charges in total that describe the Madelung potential.…”
Section: Methodsmentioning
confidence: 99%
“…Okamoto et al have theoretically studied the correlation between orbital structure and magnetism based on the model with the e g orbitals under strong electron correlation, and found that there exists an optimal mixing between the 3z 2 Kr 2 and x 2 Ky 2 orbitals for ferromagnetic ordering [14]. In the previous papers, we showed the capability of magnetic Compton profile (MCP) measurement to investigate the Mn-3d orbital state in bilayer manganites from the viewpoint of orbital occupation [15], and also reported the temperature dependence of e g and t 2g orbital populations [16]. In the presnt study, the anisotropy of MCP has been measured in the FM-II, FM-I and canted AFM phases of bilayer manganites, and the results are examined by comparison with theoretical and experimental works obtained by different methods.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The discovery of colossal magneto-resistance in the x = 0.4 bilayer 1 triggered a flurry of interest in this compound 2 . Following this, numerous studies have been conducted on the x = 0.5 doping level, showing strong charge and orbital order order.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, here, that magnetic Compton scattering is a unique probe for spin-polarized electron moment distribution ferromagnetic materials, and its cross section is proportional only to spin component of magnetization. [7][8][9][10][11] In the present studies, we have tried to evaluate the magnetic Compton profiles (MCPs) of the BCMO ceramic samples using the magnetic Compton scattering technique, in order to clarify their ferromagnetic origin. The valence state of the B-site ions was also checked by a soft X-ray photoelectron spectroscopy (XPS).…”
mentioning
confidence: 99%